Symbol, Myth, and Culture: Essays and Lectures of Ernst Cassirer 1935-1945 - Cassirer, Ernst 1874-1945; Verene, Donald P. (New Haven, CT London Yale University Press, 1979)
The papers in this volume of Ernst Cassirer's unpublished works give insight into the major issues that engaged Cassirer's interest between 1935 and 1945. Ernst Cassirer has been read and studied by generations of students, and in this book they will find illuminations, in a more informal voice, of the major themes in Cassirer's work. New readers will be introduced to the great issues that occupied the interest of one of the twentieth century's most widely read
Keywords: 20th Century (1901-2000); Philosophy